Molecular typing among poultry isolates of Salmonella agona by PCR-based techniques and pulsed field gel electrophoresis (PFGE) - Abd Mutalib, Sahilah; Radu, Son; Lum, Keng Yeang; Lihan, Samuel (Malaysian Agricultural Research and Development Institute (MARDI), 2003)
Nine genomic DNA of Salmonella agona isolated from poultry sources were characterised by three variations of PCR-based techniques [polymerase chain reaction (PCR)-ribotyping, enterobacterial repetitive intergenic consensuspolymerase chain reaction (ERIC-PCR), and random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR)] and pulsed field gel electrophoresis (PFGE). These isolates originated from three different states of Peninsular Malaysia (Pulau Pinang, Negeri Sembilan and Selangor). The results of PCR-ribotyping, ERIC-PCR, RADP-PCR and PFGE to differentiate between nine isolates of S. agona were compared. The isolates were separated into three different genome types by PCR-ribotyping, nine and eight genome types by ERIC-PCR and PFGE, respectively.